Tailored synthesis of banana stem-derived activated carbon sponge for the efficient adsorption of industrial dye - Nitin Kumar; Vanish Kumar; Vinod Kumar Garg (Next Materials)
This study reported the preparation of an activated-carbon sponge (ACS) from the banana stem (Rasthali species) for the adsorptive removal of brilliant green. Two types of ACS-materials were designed by providing inert and non-inert conditions during synthesis. Among the developed materials, ACS-7 and B were the best-performing materials prepared under inert and non-inert environments, respectively. Both the materials were characterized using XRD, FTIR, Fe-SEM, Zeta potential, and BET techniques. ACS-7 was found to be more porous with a higher surface area in comparison to ACS-B. Notably, as per kinetic studies, significant dye adsorption was observed at the initial stage of experiments. Moreover, within first 100 min, both the materials exhibited > 90 % removal rate for brilliant green. However, with the increase in the dye concentration, the efficiency of ACS-B was decreased as compared to ACS-7. Both the best-performing materials followed the Langmuir isotherm model, indicating single-layer adsorption of brilliant green on the adsorbent surface. ACS-7 and B exhibited exceptionally high maximum adsorption capacities of 1448.1 mg/g and 856.6 mg/g, respectively, which confirms that inert conditions are crucial for the development of efficient ACS material-based adsorbent. Moreover, as per GREEnness calculator, the current method is environment friendly and safer for humans. Overall, the developed ACS materials can be considered as an efficient option for the adsorptive removal of industrial dyes.